The Golden Rain of Pushyk’s Poems - Slonovska, Olha (Journal of Vasyl Stefanyk Precarpathian National University, 2020)
Pushyk S. Ya dlia Vkrainy Zhyv: u 2 t. [For Ukraine I lived: in 2 vols.] / Olha Slonovska, editor and author of foreword “Zolotyi Doshch Pusykovykh Poezii” [The Golden Rain of Pushyk’s Poems]. Misto-NV, Ivano-Frankivsk, 2019.